National Eye Institute Visual Function Scale in Type 2 Diabetes Patients. (21st February 2016) - Akkaya, Sezen; Düzova, Sinay; Şahin, Özlem; Kazokoğlu, Haluk; Bavbek, Tayfun
Abstract : Aim . To examine subscale and total scores of NEI-VFQ questionnaire of type 2 diabetes patients at different diabetic retinopathy (DRP) stages. Methods . A total number of 201 patients have been included. Prior to ophthalmological examination all patients participated in the NEI-VFQ questionnaire. The patients were divided into 5 groups according to the International Clinical Diabetic Retinopathy Disease Severity Scale (ICDRS). Results . The diabetes duration in general health scores (p = 0.029 ); the stage (p = 0.011 ); and clinically significant macular edema (CSME) (p = 0.019 ) in general vision were found to be the most efficient factors. In near vision activities the most efficient factors were near vision acuity (NVA) (p = 0.0001 ) and DRP stage (p = 0.020 ). EDTRS visual acuity was found to be the most efficient factor in vision specific role difficulties (p = 0.034 ) and dependency (p = 0.011 ) whereas Snellen visual acuity was found to be among the most effective factors in distance activities (DA) (p = 0.014 ) and total scores (p = 0.026 ). Discussion . Difference was based not on the diabetes duration, clinically significant cataract (CSCat), CSME presence, and DRP stage but on the visual acuity levels of the better seeing eye of the patients.